2010
DOI: 10.1002/jcp.22426
|View full text |Cite
|
Sign up to set email alerts
|

Whether to target single or multiple CDKs for therapy? That is the question

Abstract: Complexes consisting of cyclin-dependent kinases (CDKs) and their regulatory subunits (the cyclins) control the progression of normal mammalian cells through the cell cycle. However, during malignant transformation this regulatory apparatus malfunctions, allowing cells to undergo unchecked proliferation. In many cases, the high mitotic potential of malignant cells is due to the constitutive activation of CDK-cyclin complexes, facilitated by the inactivation of cellular CDK inhibitors, such as p16(INK4A) or p27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 121 publications
0
31
0
1
Order By: Relevance
“…In addition, selective inhibitors are in need for targeting tumors where a single kinase is aberrantly regulated. 88,89 Currently, a few ATP-competitive CDK4/6 dual inhibitors, i.e., Palbociclib (PD0332991), Ribociclib (LEE011) and Abemaciclib (LY2835219) are undergoing clinical trials. Mechanistically, these drug candidates inhibit CDK4/6, halt Rb phosphorylation and arrest G1 cell cycle progression of cancer cells.…”
Section: Structural Features and Regulationmentioning
confidence: 99%
“…In addition, selective inhibitors are in need for targeting tumors where a single kinase is aberrantly regulated. 88,89 Currently, a few ATP-competitive CDK4/6 dual inhibitors, i.e., Palbociclib (PD0332991), Ribociclib (LEE011) and Abemaciclib (LY2835219) are undergoing clinical trials. Mechanistically, these drug candidates inhibit CDK4/6, halt Rb phosphorylation and arrest G1 cell cycle progression of cancer cells.…”
Section: Structural Features and Regulationmentioning
confidence: 99%
“…application of antibiotics, corticosteroids, purine analogs and monoclonal antibodies. [7][8][9][10][11] The combined therapy of purine analogs with alkylator significantly increased patients' response to administered therapy. 8,10,11 There are a large number of new anticancer compounds currently undergoing preclinical or clinical tests.…”
Section: Introductionmentioning
confidence: 99%
“…12 Some of them reflect their action toward uncycling and cycling cell populations. 6,7,12 Despite the increasing number of clinical diagnostic parameters and overall improvement of patients' response to therapy, there are still patients who display a poor reaction to administered drugs. 13,14 The results revealed that in the group of CLL patients treated previously with chlorambucil or fludarabine, an reveal their predictive value for clinical response for CLL patients much earlier, after ex vivo testing of their PBMC sensitivity to planned treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…It is in this deeper mechanistic understanding of the executive 'enzymatic engines' of the mammalian cell division cycle (Schwartz and Shah, 2005;Marretta and Ales, 2010), that the drug targets of a more effectual apothecary for both vascular proliferative disorders (Charron et al, 2006) and otherwise intractable cancers can be found (Johnson and Shapiro, 2010;Krystof and Uldrijan, 2010). Located at the headwaters of oncogenesis, where growth-promoting proto-oncogenes meet and physically inactivate the predominant endogenous tumor suppressor proteins (Sherr and McCormick, 2002), a class of inducible regulatory proteins called "Cyclins" residealong with their Cyclin-dependent, proline-directed protein kinase (CDK) partners (Hall and Vulliet, 1991;Pines, 1995) and their respective polypeptide CDK inhibitors, which themselves represent a potent form of physiological growth inhibition/tumor suppression (Viallard, et al, 2001;Wesierska-Gadek et al, 2011). In the course of the mammalian cell division cycle, the Cyclins appear in a sequential manner, in accordance with the progressive stages of the cell cycle [note, the alphabetical designation Cyclins A through G denotes the order of scientific discovery/cloning, rather than the temporal induction of the gene product per se], participating directly in the enzymatic activation of one or more cognate CDKs (Gerard and Goldbetter, 2009) while physically guiding the activated protein kinase complexes to specific substrates (first demonstrated by Peeper et al, 1993) and subcellular locations (Morgan, 1997).…”
Section: Setting the Stage -Targeting Metastasis One Of The Gravest mentioning
confidence: 99%